Crude-Currency : An Economic Perspective on the Interrelation Between Oil Prices and Exchange Rates - Mittal, Arjun; Mittal, Anand; Das, Hritwiza; Joshi, Deepankar; Sheet, Sourabh (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : This study aimed to investigate the relationship between oil prices and exchange rates from January 2008 to December 2023. The study has been conducted using West Texas Intermediate (WTI) crude oil prices expressed in US dollars. Methodology : Granger causality and vector autoregression (VAR) models were employed to understand the interdependencies between these variables. Findings : In July of 2008, oil prices hit an all-time high of $147 a barrel. But from its 2008 high, the price fell by about 70%, with a low of $39.09 per barrel in February 2009. In 2014, the price of a barrel of oil dropped below $50. The global epidemic caused the price of oil to drop sharply in 2020 to a low of $11.26 per barrel. Since then, the price has been gradually rising. As of February 27, 2024, the WTI crude oil price was $78.78 per barrel. On the other hand, since 2008, the value of the US dollar has steadily increased. The study’s conclusions showed a significant inverse relationship between the US dollar’s value and crude oil prices. Practical Implications : The results suggested potential implications for various stakeholders. The traders could utilize the negative correlation between oil prices and exchange rates to formulate their trading strategy and diversify their portfolios. Speculators could capitalize on the trade patterns, while arbitrageurs can identify price differentials to earn profit. Policymakers and regulators can make well-informed judgments about foreign exchange and the energy market by examining their interdependencies. Originality : The study examined large datasets in addition to analyzing the relationship between oil prices and the US dollar exchange rate over a long period to gain a thorough understanding of the relationships between oil prices and other currencies. Additionally, the research helps us understand the implications of events like the 2014 oil price fall as well as the long- and short-term patterns.